Mountain Top Mystery : The Boxcar Children #9 - Gertrude Chandler Warner (U.S.A. Albert Whitman & Company)
Marooned on a mountain, the Aldens survive a landslide and find a Native American secret.
Keywords: Mystery -- Mystery